Financial Performance in Portuguese Outdoor Tourism Industry: A Quantitative Research - Sadiksha BARAL; Sadikshya BHATTARAI; Nuno MOUTINHO; Alcina NUNES; Paula Odete FERNANDES (Communications of International Proceedings, 2022)
Tourism is a vital industry in south European countries, like Portugal, where outdoor tourism is growing. Understanding the macroeconomic importance of outdoor tourism in the Portuguese economy, it is also noticeable there are fewer studies regarding the profitability of outdoor companies. Therefore, this paper investigates the financial determinants influencing the profitability of Portuguese outdoor tourism companies for the period 2010 to 2020. The results from an OLS regression allow finding evidence that companies working capital and financial autonomy are positively related to company performance. Moreover, size is negatively associated with the companies' performance in this industry. Leverage and sales growth seem not relevant to ensuring outdoor companies' profitability. The results also show that companies' location is not important in explaining the performance of outdoor tourism companies.
Keywords: Outdoor Tourism; Companies' Performance; Portugal